Local communities’ willingness to pay for increasing the status of a Forest Reserve in Ghana to a National Park - Michael Ansong; Joana Akua Serwaa Ameyaw; Kwadwo Boakye Boadu; Sedomda Kpikpitse; Emmanuel Acheampong (Social Sciences and Humanities Open, 2023)
Atewa Forest Reserve is a Globally Significant Biodiversity Area and Important Bird Area in Ghana. The reserve has lost over 10% and 35% of its close canopy and buffer zone respectively in the last twenty years. Increasing the status of the reserve to a National Park with a buffer zone has been recommended as the key intervention that could help achieve a more optimal flow of its benefits to people. It is, however, not clear if fringe communities whose livelihoods are directly linked to the reserve will support such intervention. To provide an indication of their potential level of support and appreciation of this recommendation, we used contingent valuation method with the double-bounded dichotomous choice approach and an open ended follow up question to estimate willingness to pay of members in the fringe communities. The majority were willing to donate a day's wage for 12 months to support the project if implemented. The estimated mean willingness to pay was Ghȼ 9.99, (US$ 2.22). Respondents' income level, age and initial bid offered are the main factors that influence respondents' willingness to pay. The policy implication and importance of understanding socio-economic characteristics of households in the process of designing such intervention is discussed in the paper.